Neuroprotective effect of selected herbs on H2O2-induced neuroblastoma cell damage in SH-SY5Y / Farah Azirah Mohd Yusuf - Farah Azirah , Mohd Yusuf (2019)
Neurodegenerative diseases occur as a result of the chronic breakdown and deterioration of neurons. Oxidative stress resulting from free radical formation by reactive oxygen species (ROS) and reactive nitrogen species (RNS) is known to be the main causative factor in the initiation of neurodegeneration. A number of current therapeutic approaches lead to the upsurge of undesirable side effects. Hence, a great deal of attention has been focused on the use of natural antioxidant from plants to protect neuronal cells from oxidative damage or death which can lead to a number of neurodegenerative diseases. The present work was designed to establish the neuroprotective effect of selected herbs; Piper betle L. and Clitoria ternatea L., on hydrogen peroxide (H2O2) -induced neuronal cell damage on human neuroblastoma SH-SY5Y cells. The leaves of P. betle and C. ternatea were subjected to extraction method using methanol and water to yield methanolic and water extract. In prior to the neuroprotective assay, toxicity test on dimethyl sulfoxide (DMSO) as solvent, H2O2 as oxidative stress agent and, the plant extracts were analysed. The results were presented as percentage of cell viability which was assessed using MTT assay after each of the experiment. Total phenolic (TPC) and flavonoid contents (TFC) of the herbal extracts were quantified by colorimetric assay. Antioxidant capacity of the herbal extracts were assessed through 1, 1-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2‟-Azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) [ABTS] free radical scavenging assay. Relationship between neuroprotective activity, TPC, TFC, DPPH and ABTS scavenging activity was analysed through correlation coefficient analysis. The neurotoxicity test of the extracts revealed that the extracts of P. betle were toxic towards SH-SY5Y cells when the concentration used was >10 μg/mL, meanwhile the extracts of C. ternatea were not toxic to the cells at the range of concentration tested (1–100 μg/mL). Matching with the toxicity results, P. betle extracts show significant neuroprotective activity at lower concentrations (0.001–10 μg/mL). C. ternatea extracts also show good neuroprotective activity at the respective range of concentration tested (1–100 μg/mL). The present work also found that the methanolic extract of P. betle show better neuroprotective effect in pre-treatment group and its water extract in post-treatment group, suggesting that this plant might be suitable for prevention and treatment respectively in neurodegenerative disease management. Meanwhile for C. ternatea extracts, the results revealed that this plant might be suitable to be used as prevention in managing neurodegenerative diseases. The extracts of P. betle were also shown to record greater TPC, DPPH and ABTS free radical scavenging activity, while the extracts of C. ternatea was found to have higher TFC. Furthermore, correlation analysis between neuroprotective activity, TPC, TFC, DPPH and ABTS radical scavenging capacity for the extracts of P. betle demonstrated negative correlations, meanwhile C. ternatea provided positive correlations. Correlation analysis between TPC, TFC, DPPH and ABTS showed positive correlation. In conclusion, current findings suggest that P. betle and C. ternatea possess good phenolic, flavonoid and antioxidant capacity, and ameliorated H2O2-induced neuronal cell death in dose-dependent manner. Therefore, these herbs have potential for development as neuroprotective agent to be used as alternative or complementary therapy in neurodegenerative diseases management.